2006
DOI: 10.4103/0970-4388.26025
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and orthodontic treatment of an impacted permanent central incisor: A case report

Abstract: Although impaction of a permanent tooth is rarely diagnosed during the mixed dentition period, an impacted central incisor is usually diagnosed accurately when there is delay in the eruption of tooth. In this article, the impacted incisor was moved into it's proper position with surgical exposure and orthodontic traction, after which it showed good stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
6
0
6
Order By: Relevance
“…Several clinicians have successfully treated impacted maxillary anterior teeth by proper crown exposure surgery and orthodontic traction and indicated that an impacted tooth can be brought to proper alignment in the dental arch. (10)(11)(12) The current treatment modality instead of extraction has used surgical crown exposure and orthodontic positioning of the tooth. Factors considered for successful alignment of an impacted tooth: The position and the direction of impacted tooth, degree of root completion and presence of space for impacted tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinicians have successfully treated impacted maxillary anterior teeth by proper crown exposure surgery and orthodontic traction and indicated that an impacted tooth can be brought to proper alignment in the dental arch. (10)(11)(12) The current treatment modality instead of extraction has used surgical crown exposure and orthodontic positioning of the tooth. Factors considered for successful alignment of an impacted tooth: The position and the direction of impacted tooth, degree of root completion and presence of space for impacted tooth.…”
Section: Discussionmentioning
confidence: 99%
“…However, they reported that aesthetic results were achieved at the end of the treatment. Similarly, Thosar and Vibhute [1], Kalaskar and Kalaskar [18] did not use the closed-eruption surgical technique in their cases. In our case, after 2 years of follow-up, a stable occlusion was maintained with only minor relapse at the right central incisor.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth impaction may result from a number of local causal factors. These include arch length discrepancy, ectopic positioning of the teeth, presence of supernumerary teeth, mucosal or bony barriers, and retained deciduous teeth [1,2]. The prevalence of supernumerary teeth was found to be 2.7 in a sample of Turkish children, and the most commonly encountered supernumeraries were mesiodens (51.0%) [3].…”
Section: Introductionmentioning
confidence: 97%
“…Harus diperhatikan pemilihan braket yang layak digunakan dan persiapan tempat yang memadai sehingga posisi kaninus yang baik dapat tercapai. 3 Thosar 11 ,melaporkan keberhasilan perawatan impaksi dengan menggunakan surgical exposure pada anak laki-laki berusia 10 tahun dengan impaksi pada insisivus sentral permanen rahang atas kiri di Departemen Kedokteran Gigi Anak , Universitas Sharad Pawar India. Sebelum dilakukan surgical exposure dipertimbangkan beberapa faktor yaitu posisi dan arah gigi impaksi, keadaan apeks dan adanya ruang untuk gigi yang impaksi.…”
Section: Teoriunclassified